Analysis of Smoking and Alcohol Consumption Behavior as Risk Factors for Non-Communicable Diseases in the Productive Age Group - Andi Nur Arifah Apriani Azis (PT. Anagata Sembagi Education, 2025)
Smoking and alcohol consumption among productive-age adults represent major behavioral risk factors contributing to the rising burden of non-communicable diseases (NCDs), including cardiovascular diseases, stroke, cancer, diabetes, and chronic respiratory disorders. This study aims to analyze behavioral patterns, determinants, and the health impacts of smoking and alcohol consumption among individuals aged 25–54 years. A descriptive qualitative method with an analytical literature study approach was employed, reviewing reputable scientific publications from 2015 to 2024. Findings indicate that smoking and alcohol consumption in productive-age populations are driven by workplace stress, social norms, cultural influences, and urban lifestyle shifts. The combination of both behaviors exponentially increases NCD risks through inflammatory mechanisms, oxidative stress, metabolic dysregulation, and organ damage. Social determinants such as economic pressure and mental health also contribute to sustained risky behaviors. This study recommends multi-level interventions including education, counseling, enhanced health literacy, workplace wellness programs, and public health policies such as increased tobacco taxation and alcohol access restrictions.